Interface Microstructure and Mechanical Properties of Nickel/Steel Bimetal Composite Pipe Fabricated by Explosive Welding - Yuwei Sun; Sirong Yu; Bingying Wang; Lin Liu; Enyang Liu; Tao Feng (Metals)
In this paper, the microstructure and mechanical properties at the interface of Incoloy825/X65 bimetallic composite pipe achieved by explosive welding were systematically studied. Results show that a periodic wavy bonding interface was formed between the Incoloy825 and X65 due to the jets caused by the high-impact stresses during explosive welding, which was beneficial for improving the bonding strength of the Incoloy825 and X65. Atomic diffusion and localized melting occurred near the interface during explosive welding. Some fine crystal grains were generated in the vicinity of the interface due to the strong plastic deformation and dynamic recrystallization, whereas some elongated grains growing in the perpendicular direction to the interface were found in the wider localized melted zone. Room temperature nanoindentation test showed that due to the existence of fine grains resulting from the recrystallization at the interface, the hardness of the interface was higher than that of the base metals. Voids and defects were prone to appearing in the vortex regions near the interface, where the weak point in the interface was located.